Eruptive Xanthoma in Acute Pancreatitis: A Systematic Review of Case Reports - Yonatan, Eric Ricardo; Alexander, Leonardo; ., Valencia; Wijaya, Lorettha (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
Background: Eruptive xanthoma is a skin lesion caused by localized lipid deposits in the dermis, characterized by an eruption of yellow papules typically present on the buttocks, shoulders, and extensor skin surfaces of the extremities. Eruptive xanthoma is associated with acute pancreatitis as a result of hypertriglyceridemia or other lipid disorders. This study aims to discuss several case reports of patients with eruptive xanthomas and acute pancreatitis to provide descriptions and similarities between cases.Methods: This systematic review was conducted using Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines. Case reports about eruptive xanthoma and acute pancreatitis are included in this systematic review. The literature search was done using PubMed, EBSCOHost, ProQuest, and Google Scholar. Critical evaluation for case reports by Joanna Briggs Institute is used for risk of bias assessment.Results: A literature search identified 6 case reports after eliminating irrelevant and duplicated studies. All assessed case reports reported similar dermatologic manifestations of eruptive xanthoma. Majority of patients reported severe acute abdominal pain as the main symptom of acute pancreatitis. All studies showed an increased level of lipid profiles, and other diagnostic workups support the diagnosis of eruptive xanthoma and acute pancreatitis. Risk of bias in case reports included was acceptable.Conclusion: Eruptive xanthomas can be found in patients with acute pancreatitis with correlation to hypertriglyceridemia and lipid disorders. Proper recognition, diagnosis, and treatment for eruptive xanthoma and acute pancreatitis should be kept in mind for practitioners.Keywords: Eruptive xanthoma, acute pancreatitis, systematic review